(untitled) (Praxis Educativa, 2025)
Along with the digitalization of everyday life, social reality has become a intertwined web of face-to-face and digital interactions and mobilities, both intrinsically corporeal and digital. Despite technological access gaps, young people make ubiquitous use of ICT in all aspects of their lives. Building on the premises of the mobilities paradigm, and through participatory mapping workshops with high school students from the urban periphery of Córdoba, we analyze youth mobilities in digital environments. Specifically, the ways in which these mobilities overlap, replace, or support schoolwork. The findings suggest that digital mobilities may be mitigating some territorial limitations that are usually documented, and that certain digital environments and practices amplify the “school mesh”; maximizing youth autonomy in relation to parental and adult control. They also allow for a discussion of the prevailing diagnosis of “dispersion” and “zapping” in the literature on ICT use in schools